2018
DOI: 10.18632/oncotarget.24374
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of three polygenic risk score models for the prediction of breast cancer risk in Singapore Chinese

Abstract: Genome-wide association studies (GWAS) have proven highly successful in identifying single nucleotide polymorphisms (SNPs) associated with breast cancer (BC) risk. The majority of these studies are on European populations, with limited SNP association data in other populations. We genotyped 51 GWAS-identified SNPs in two independent cohorts of Singaporean Chinese. Cohort 1 comprised 1294 BC cases and 885 controls and was used to determine odds ratios (ORs); Cohort 2 had 301 BC cases and 243 controls for derivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 59 publications
1
16
0
Order By: Relevance
“…We compared the predictive performance of the 287-SNP PRS for overall breast cancer with five PRSs 15 , 17 , 19 , 26 , 27 , which were previously developed or evaluated using data from Asian populations. Of these 5 PRSs, one was developed using iCogs genotyped studies in BCAC and 744 samples from MyBrCa study 15 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We compared the predictive performance of the 287-SNP PRS for overall breast cancer with five PRSs 15 , 17 , 19 , 26 , 27 , which were previously developed or evaluated using data from Asian populations. Of these 5 PRSs, one was developed using iCogs genotyped studies in BCAC and 744 samples from MyBrCa study 15 .…”
Section: Resultsmentioning
confidence: 99%
“…We compared the predictive performance of the European ancestry-based PRS with PRSs that were previously developed or evaluated in Asian populations. The five Asian ancestry-derived PRSs included 5 SNPs 15 , 51 SNPs 17 , 44 SNPs 19 , 6 SNPs 26 and 46 SNPs 27 . The PRSs were derived using Eq.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, our analysis was restricted to survivors of European ancestry and thus there is a need to assess risk associated with rare P/LP mutations and common variants (i.e. PRS) within other non-European ethnic groups(1922).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there are some studies that showed that PRS can improve the discrimination in Asian women above existing risk models [ 56 58 59 60 61 ]. For example, Shieh et al showed that a PRS comprised of 76 SNPs improved the AUC of the BCSC model in East Asian women in San Francisco, California from 0.62 (95% CI, 0.59–0.66) to 0.72 (95% CI, 0.62–0.82) [ 48 ].…”
Section: Toward Personalized Breast Cancer Screening In Korea: Incorpmentioning
confidence: 99%